Elections And Development Of Democracy In Indonesia - Nur Fadillah; Didik Himmawan; Ahmad Khotibul Umam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of this research is to find out about General Elections and the development of democracy in Indonesia. This research applies library methods, which are often referred to as library studies. This method is an effort by researchers to collect material related to research topics or problems from various sources, including books, scientific reports, theses, theses, dissertations, encyclopedias, and other sources, both in print and digital form. The results of this research are, the purpose of elections and the democratic nature of an election for the sake of developing democracy, there are also functions of elections that cannot be separated from each other, namely (1) As a means of political legitimacy, especially the need for the government and the political system to obtain sources of authority and its political power. (2) The function of people's representatives. Simultaneous national elections have a number of hypothetical advantages from the perspective of political institutionalization and democratic consolidation in Indonesia. (3) Simultaneous national elections encourage a more democratic quality of political parties.